Parceria pública privada para qualificação de mão de obra: o caso do município de Telêmaco Borba/PR - Oliveira, Juliano Xavier de (2013)
It is known that the Telêmaco Borba city has a specific need for labor related demands that industry pulp and paper requires. The government, however, presents itself unable to meet this demand and the satisfaction through the Public Private Partnership opens up possibilities. Thus, this study was to analyze the thematic importance of the qualification of manpower for the labor market. We intend to seek to respond effectively what benefits this partnership brings to the municipality. This is a current issue at national level and relevant to the local context and can help bring clarity to future decisions regarding the expansion of partnerships between the public and private spheres. The work is based on laws and theoretical foundation for the research and for better understanding, consists of a study on Public Policy, Public Private Partnerships, the qualification of the workforce in the public sector and public-private partnerships qualification of manpower. It also presents a field study carried out in the Bureau of Labor and Industry Conventional and Technical Coordination of National Apprenticeship Service (SENAI) through an interview with representatives of these sectors. Thus, in this way, we intend to disseminate greater clarity on the subject still incipient in our midst.